PENGARUH PENGALAMAN KERJA, INTEGRITAS DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT PADA AUDITOR INSPEKTORAT SE-EKS KARISIDENAN SURAKARTA - Aprilia, Shelly; Kristianto, Djoko; Sunarti, Sunarti (Universitas Slamet Riyadi, 2021)
The research objectives are 1) to analyze the auditor work experiencevariable which has a positive effect on audit quality; 2) Analyzing auditorintegrity variables have a positive effect on audit quality; 3) Analyzing theauditor's accountability variable has a positive effect on audit quality. This type ofresearch is survey research using a quantitative approach, where data analysis iscarried out in this study by performing statistical calculations. The samplingtechnique uses positive random sampling. The population in the study were allauditors who worked at the City / Regency Inspectorate of the former SurakartaResidency which included the Surakarta City Inspectorate, the Boyolali RegencyInspectorate, the Klaten Regency Inspectorate, the Sukoharjo RegencyInspectorate, the Wonogiri Regency Inspectorate, the Karanganyar RegencyInspectorate, the Sragen Regency Inspectorate. The sample of this research is allauditors of the Inspectorate throughout the Surakarta Residency as many as 83.The results of the study show that: 1) Work experience has a significanteffect on audit quality, meaning that the increasing work experience will alsoincrease the quality of the audit. Therefore, the higher the work experience theauditor has, the better the audit quality will be. 2) Integrity has a significant effecton audit quality, meaning that the increasing integrity of auditors will alsoincrease the quality of the resulting audit. Therefore, the higher the integrity ofthe auditor, the better the quality of the audit provided. 3) Accountability has asignificant effect on audit quality, meaning that the higher the auditor'saccountability, the better the quality of the audit will be performed and the auditquality can be achieved if the auditor has good accountability. So that if theauditor has high accountability, the results of the assessment will be of highquality.